Healthcare resource use of patients with transthyretin amyloid cardiomyopathy - Rosa Lauppe; Johan Liseth Hansen; Anna Fornwall; Katarina Johansson; Mark H. Rozenbaum; Anne Mette Strand; Merja Vakevainen; Johanna Kuusisto; Einar Gude; J. Gustav Smith; Finn Gustafsson (ESC Heart Failure)
Abstract Aims Transthyretin amyloid cardiomyopathy (ATTR‐CM) is the cardiac manifestation of transthyretin amyloidosis (ATTR). The aim of this study was to estimate healthcare resource use for ATTR‐CM patients compared with heart failure (HF) patients, in Denmark, Finland, Norway, and Sweden. Methods and results Data from nationwide healthcare registers in the four countries were used. ATTR‐CM patients were defined as individuals diagnosed with amyloidosis and cardiomyopathy or HF between 2008 and 2018. Patients in the ATTR‐CM cohort were matched to patients with HF but without ATTR‐CM diagnosis. Resource use included number of visits to specialty outpatient and inpatient hospital care. A total of 1831 ATTR‐CM and 1831 HF patients were included in the analysis. The mean number of hospital‐based healthcare contacts increased in both the ATTR‐CM and HF cohort during 3 years pre‐diagnosis and was consistently higher for the ATTR‐CM cohort compared with the HF cohort, with 6.1 [CI: 5.9–6.3] vs. 3.2 [CI: 3.1–3.3] outpatient visits and 1.03 [CI: 0.96–1.1] vs. 0.7 [CI: 0.7–0.8] hospitalizations. In the first year following diagnosis, patients with ATTR‐CM continued to visit outpatient care (10.2 [CI: 10.1, 10.4] vs. 5.7 [CI: 5.6, 5.9]) and were admitted to hospital more frequently (3.3 [CI: 3.2, 3.4] vs. 2.5 [CI: 2.5, 2.6]) than HF patients. Conclusions Transthyretin amyloid cardiomyopathy imposes a high burden on healthcare systems with twice as many outpatient specialist visits and 50% more hospitalizations in the year after diagnosis compared with HF patients without ATTR‐CM. Studies to investigate if earlier diagnosis and treatment of ATTR‐CM may lower resource use are warranted.